Criminal Profiling Kasus Pembunuhan Dan Pemerkosaan Studi Kasus Eno Farihah (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Criminal Profiling is an investigative technique to describe the profile of criminals in terms of demographics, psychology, modus operandi and incident settings. In this article, researchers are interested in carrying out Criminal Profiling on the murder and rape cases of Eno Farihah, to see an overview of the Criminal Profiling that occurred in that case, the factors of the murder and rape of the perpetrators, and the profiling of each perpetrator in the case concerned. The research method that researchers use is literature review and literature research. From the findings of the researchers it is known that the murder case of Eno Farihah by three perpetrators had different reasons. The RA perpetrator was the victim's boyfriend who was involved because the victim refused his invitation to have sex, while the RAr perpetrator was suspected because he was often ridiculed bitterly and blackly, then the last perpetrator IH was allegedly because of unrequited love. So that the perpetrators were charged under the applicable law with different legal sentences, the perpetrators RAr and IH were sentenced to death, while the perpetrators RA were sentenced to 10 years in prison because they were underage.